Evaluation of High-Performance Pervious Concrete Mixed with Nano-Silica and Carbon Fiber - Mingxuan Sun; Meng Sun; Yunlong Zhang; Lijun Ma (Buildings, 2025)
To address the mechanical deficiencies of traditional pervious concrete and promote its practical implementation, this study developed a high-performance pervious concrete model using conventional materials and methods, achieving a permeability coefficient of 4.5 mm/s with compressive and flexural strengths exceeding 45 MPa and 5 MPa, respectively. Central composite design (CCD) response surface methodology was employed to investigate the individual and synergistic effects of the water–cement ratio (W/C), nano-silica (NS), and carbon fibers (CF) on permeability, compressive strength, and flexural strength. Statistical models demonstrating prediction errors within 7% of experimental values were established, supplemented by a microstructural analysis of the concrete specimens. The results demonstrated that (1) the W/C ratio significantly influences overall performance; (2) NS enhances mechanical strength while reducing permeability, though excessive NS content induces weak interfacial zones that compromise strength; (3) CFs exhibit negligible impact on compressive strength but substantially improve flexural performance; and (4) significant synergistic interactions are present across W/C ratio, NS, and CFs concerning flexural strength parameters, while no significant interaction was observed for compressive strength.